Nitrogen Metabolism in Adaptation of Photosynthesis to Water Stress in Rice Grown under Different Nitrogen Levels - Zhong, Chu; Cao, Xiaochuang; Hu, Jijie; Zhu, Lianfeng; Zhang, Junhua; Huang, Jianliang; Jin, Qianyu (Frontiers in Plant Science, 2017)
To investigate the role of nitrogen (N) metabolism in the adaptation of photosynthesis to water stress in rice, a hydroponic experiment supplying with low N (0.72 mM), moderate N (2.86 mM), and high N (7.15 mM) followed by 150 g·L-1 PEG-6000 induced water stress was conducted in a rainout shelter. Water stress induced stomatal limitation to photosynthesis at low N, but no significant effect was observed at moderate and high N. Non-photochemical quenching (NPQ) was higher at moderate and high N. In contrast, relative excessive energy at PSII level (EXC) was declined with increasing N level. Malondialdehyde (MDA) and hydrogen peroxide (H2O2) contents were in parallel with EXC. Water stress decreased catalase (CAT) and ascorbate peroxidase (APX) activities at low N, resulting in increased H2O2 content and severer membrane lipid peroxidation; whereas the activities of antioxidative enzymes were increased at high N. In accordance with photosynthetic rate and antioxidative enzymes, water stress decreased the activities of key enzymes involving in N metabolism such as glutamate synthase (GOGAT) and glutamate dehydrogenase (GDH), and photorespiratory key enzyme glycolate oxidase (GO) at low N. Concurrently, water stress increased nitrate content significantly at low N, but decreased nitrate content at moderate and high N. Contrary to nitrate, water stress increased proline content at moderate and high N. Our results suggest that N metabolism appears to be associated with the tolerance of photosynthesis to water stress in rice via affecting CO2 diffusion, antioxidant capacity, and osmotic adjustment.